ANALISIS SEMIOTIKA PADA LIRIK LAGU MINANG “TARAGAK PULANG “ KARYA DIRA SATI DI TIKTOK - Rika Handayani; Sabri (Jurnal Ilmu Komunikasi Balayudha, 2024)
This research was conducted to find out the meaning of the lyrics of the song Taragak Pulang Karya dira sati. This study uses qualitative methods with the theory of semiotic analysis of the Ferdinand de Saussure model. Data is obtained by grouping song lyrics into several stanzas and then looking for markers and signifieds in the song. This song contains an expression of the longing of a nomad who misses his hometown but this longing has not been paid off. as well as a message for migrants so they can be enthusiastic about making a living abroad and as a message for families left behind not to worry about the condition of their children who are far away overseas.